Prevalence and C-shaped root canal configuration in lower molars in the metropolitan region, Chile. - Fernando Peña-Bengoa; Juan Contreras-San Martín; Patricio Meléndez-Rojas (Universidad de Concepción., 2022)
Objetive: The aim of this study was to determine the prevalence, demographics, and root configuration of C-shaped canals of mandibular molars by means of cone beam computed tomography in the population of the Metropolitan Region, Chile. Material and Methods: 912 molars (456 first and 456 second molars) resulting from the analysis of 228 mandibular CT scans were evaluated. The root configuration was established by means of a panoramic reconstruction and axial tomographic sections, classifying the presence and type of canals through the analysis of five sections or cuts along the root. Data were statistically analyzed using a 5% confidence interval. Results: Of the 912 molars analyzed, 70 were classified as C-shaped canals (7.68%), corresponding to 58.33% of those molars that presented fused roots. 95.7% of this root canal configuration was observed in lower second molars, occurring more frequently in females (n=45, 64.29%). 45.65% of the cases that presented C-shaped canals were bilateral and the most frequent configuration was C3 (n=401, 66.63%) according to the Melton classification. Conclusion: The C-shaped canals of the mandibular molars in the studied population were observed mainly in second molars, showing a clear prevalence among females and a high percentage of bilaterality. The presence of fused roots significantly increases the possibility of finding this type of root configuration.